Characteristics of patients with meningitis after lumbar epidural steroid injection - Kang, You-Ri; Nam, Tai-Seung; Kim, Byeong C.; Kim, Jae-Myung; Cho, Soo Hyun; Kang, Kyung Wook; Choi, Kang-Ho; Kim, Joon-Tae; Choi, Seong-Min; Lee, Seung-Han; Park, Man-Seok; Kim, Myeong-Kyu (Medicine (Baltimore), 2022)
To investigate the clinical, laboratory, and radiological features of meningitis after lumbar epidural steroid injection (M-ESI) without accompanying spinal infection, data of patients with meningitis admitted between January 2014 and December 2021 in a single center were retrospectively reviewed. Among them, patients with a recent history of lumbar ESI were identified, and their medical records were collected. Patients with concomitant infections other than meningitis, including spinal epidural abscess, were excluded. Seven patients with M-ESI were identified. All patients presented with headache and fever without focal neurological deficits, and headache developed shortly after a procedure (median, 4 hours). Cerebrospinal fluid (CSF) analysis showed neutrophilic pleocytosis (median, 6729/μL), elevated protein level (median, 379.1 mg/dL), decreased ratio of CSF glucose to serum glucose (median, 0.29), and elevated lactate level (median, 8.64 mmol/L). Serum level of C-reactive protein was elevated in 6, but serum procalcitonin level was within normal range. No causative pathogen was identified in the microbiological studies. The most frequent radiologic feature was sulcal hyperintensity on fluid-attenuated inversion recovery images (57%), followed by pneumocephalus (43%). Symptoms subsided in a short period (median, 1 day) after initiating treatment with antibiotics and adjuvant intravenous corticosteroids. None of the patients experienced neurological sequelae. Though the cardinal symptoms and CSF findings of M-ESI were comparable to those of bacterial meningitis, M-ESI seems to have distinctive characteristics regarding the clinical course, laboratory parameters, and pneumocephalus.